Intrafetal alcohol ablation of an acardiac twin - Zakaria, Zahar Azuar; Ramli, Roziana; Malek, Idayu Adul; Razak, Maheran Abdul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
The twin reverse arterial perfusion (TRAP) sequence is a rare but serious complication of mono-chorionic multiple pregnancies in which the affected twin is reversely perfused from the healthy co-twin. The unaffected twin is at risk of cardiac de-compensation or complication related to polyhydramnios, preterm pre-labour rupture of membrane and preterm delivery. When the risk to the healthy fetus increases significantly, the management is to occlude the circulation to the acardiac twin. Here we report a case successfully managed with intra-fetal alcohol ablation at the mid-trimester.